Polyphenolic compounds from Idesia polycarpa Maxim. fruits ameliorate non-alcoholic fatty liver disease by modulating lipid metabolism in oleic acid-induced HepG2 cells and high-fat diet-induced mice - Lei Huang; Yanrong Zeng; Fei Li; Xiuyan Zheng; Qing Rao; Babu Gajendran; Krishnapriya M. Varier; Tong Peng; Lin Tang (Journal of Functional Foods, 2023)
Previous reports have suggested that Idesia polycarpa Maxim. (I. polycarpa) fruits possess properties for the prevention and treatment of non-alcoholic fatty liver disease (NAFLD), owing to its lipid-lowering and anti-oxidant activities. In this study, ethyl acetate extract (EAE) of I. polycarpa fruits supplementation reduced body weight gain and inflammatory cytokines secretion, improved glucose tolerance and insulin sensitivity, and alleviated hepatic steatosis in high-fat diet (HFD)-fed mice. Of note, a total of eight polyphenolic compounds were isolated and identified from EAE, among which 1-[(6′-O-(Z)-p-coumar-oyl)-β-D-glucopyranosyl]-oxy-2-phenol (compound 2) exhibited better lipid-lowering activity in oleic acid (OA)-induced HepG2 cells than other compounds. Moreover, using hepatic steatosis cell model and PPAR-luciferase reporter system, we found that compound 2 reduced lipid accumulation and lipotoxicity, and inhibited inflammatory reaction via the PPAR-α-mediated improvement of lipid metabolism. This experiment will provide a theoretical basis for intervention with I. polycarpa fruits in delaying the occurrence and development of NAFLD.